Government Accountability in Universal Services in Collaborative Regulation: A Perspective on the General Principles of Good Governance (AUPB) - Hamdani Gunawan, Arief; Ketut Rachmi Handayani, I Gusti Ayu; Karjoko, Lego (Pelopor Publikasi Akademika, 2024)
Universal telecommunication services are one of the government's efforts to ensure equitable accessibility of telecommunication services for all levels of society. However, at this time, telecommunications regulation is entering a collaborative generation, which is characterized by the cooperation of various entities to deal with the impact of the widespread digital economy. The purpose of this study is to analyze the extent to which the government has fulfilled its obligations and responsibilities in providing equitable access to telecommunications in the era of the collaborative generation. The research method used is normative juridical with a qualitative approach. The results of this study indicate that while there has been progress in implementing the General Principles of Good Governance in universal telecommunications services, challenges remain in the areas of transparency and accountability, particularly in the allocation of funds and resources. Additionally, disparities in access between urban and rural areas persist, despite collaborative regulatory efforts. The study found that government initiatives, though well-intentioned, require stronger oversight and more inclusive policies to ensure fair and equitable access to telecommunications for all segments of society.